ANALISIS PERBANDINGAN PENDAPATAN PETANI PADI SAWAH DAN JAGUNG DI DESA BONDE-BONDE KECAMATAN TUBO SENDANA KABUPATEN MAJENE - Tussadia, Halimah; Pakanyamong, Ambo Abd. Kadir; Hartina (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2025)
Paddy and corn are the main food commodities that have an important role in meeting the consumption needs of the community and as a source of income for farmers, especially in rural areas. The purpose of this study was to determine the comparison of the cost structure, production and income of rice farmers and corn farmers. The research location was in Bonde-Bonde Village, Tubo Sendana District, Majene Regency, using primary and secondary data on the comparison of the cost structure, production and income of rice farmers and corn farmers with a sample of 15 groups of rice farmers and 15 groups of corn farmers. The analysis method used was a qualitative research method using the Miles and Huberman model in analyzing the data obtained. The results of the study show that the comparison of income of rice farmers and corn farmers is very different seen from the planting patterns carried out by rice and corn resulting in differences in the resulting production, costs incurred by farmers and differences in income received by farmers, the difference in the amount of production costs of paddy rice is Rp. 9,766,543 / ha / year and income of paddy rice is 25,609,457 / ha / year while corn farming production costs are Rp. 7,964,045 / ha / year and income is Rp. 28,035,954 / ha / year. So it is known that corn farming is more profitable than rice farming. This is due to differences in land use, use of fertilizers, pesticides, and production facilities that vary so that the costs incurred by farmers are also different so that there is a comparison of differences in farming income.